Tax Incentive, Public Share Proportion, and Firm Performance: Evidence from Indonesian Capital Market - Upa, Vierly Ananta (The Indonesian Capital Market Review, 2012)
Indonesian government has changed the taxation law in 2007. The regulation revealed that companies listed on capital market can obtain reduced income tax rate by 5 percent. Decrease in income tax rates is granted to domestic corporate taxpayers listed on capital market that have public ownership over 40 percent of the total paid shares and the shares owned by at least 300 parties. The purpose of this research is to analyze the effectiveness of government regulation (PP) No. 81 of 2007. This research used companies listed on Indonesia Stock Exchange (IDX) which have right offering in 2009-2010 as a sample. Sample selection is performed based on purposive sampling method. The result indicates that government regulation related to tax incentives, which was aimed to increase the proportion of public ownership, is still less effective. In addition, this study also showed that the proportion of public ownership has no significant effect on firm performance.